Provision of paediatric and adolescent gynaecology in Europe today: A joint review by the European Association of Paediatric and Adolescent Gynaecology (EURAPAG) and European Board and College of Obstetrics and Gynaecology (EBCOG). (April 2019) - Bedei, Ivonne; Bumbuliene, Zana; Sirakov, Milko; Mahmood, Tahir; Wood, Paul L.; ,
Abstract: Paediatric and Adolescent Gynaecology (PAG) is a multidisciplinary field combining aspects of gynaecology but also includes paediatrics, endocrinology, genetics, radiology, psychology and urology. Specialist knowledge is warranted for the care of these youngsters, and it is important that doctors attending to the gynaecological needs of children must understand that they are not just "little women". Their needs and accompanying clinical approaches required are very different from those of adults in this sensitive area, as is the spectrum of diseases and problems. A multidisciplinary collaboration is as important as the establishment and adoption of standards in education, training and management. The situation in Europe in PAG is varied, reflecting the relative youth of this area of special interest and thereby allowing for earlier consolidation of standards and services across Europe. This article summarises the background to PAG in Europe, inequitable current provision of care and issues relating to education and training all of which are relevant in providing a common approach to PAG problems and endeavouring to obtain the best outcomes. There remains huge diversity how the services for "young women" are currently delivered across different countries within Europe. A concerted European approach is urgently required to streamline standards of training and clinical care, to ensure high quality care by using agreed national and European pathways.